2011
DOI: 10.1074/jbc.m110.190652
|View full text |Cite
|
Sign up to set email alerts
|

Tmprss3, a Transmembrane Serine Protease Deficient in Human DFNB8/10 Deafness, Is Critical for Cochlear Hair Cell Survival at the Onset of Hearing

Abstract: Mutations in the type II transmembrane serine protease 3 (TMPRSS3) gene cause non-syndromic autosomal recessive deafness (DFNB8/10), characterized by congenital or childhood onset bilateral profound hearing loss. In order to explore the physiopathology of TMPRSS3 related deafness, we have generated an ethyl-nitrosourea-induced mutant mouse carrying a protein-truncating nonsense mutation in Tmprss3 (Y260X) and characterized the functional and histological consequences of Tmprss3 deficiency. Auditory brainstem r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
82
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(91 citation statements)
references
References 33 publications
9
82
0
Order By: Relevance
“…In Xirp2 −/− mice, the F-actin meshwork of the cuticular plates might be looser or the failure of membrane-cytoskeletal adhesion may allow the extrusion of membrane from weaker spots in the apical surface. A similar phenotype was described in Tmprss3 Y260X mutant mice (Fasquelle et al, 2011) although the protrusions were reported to be kinocilia.…”
Section: Discussionsupporting
confidence: 67%
“…In Xirp2 −/− mice, the F-actin meshwork of the cuticular plates might be looser or the failure of membrane-cytoskeletal adhesion may allow the extrusion of membrane from weaker spots in the apical surface. A similar phenotype was described in Tmprss3 Y260X mutant mice (Fasquelle et al, 2011) although the protrusions were reported to be kinocilia.…”
Section: Discussionsupporting
confidence: 67%
“…Human genetics and loss of function studies in mice have revealed important and surprisingly diverse roles of membrane-anchored serine proteases in mammalian development and postnatal homeostasis. These include placental morphogenesis [4, 5], neural tube closure [6], epithelial tight junction formation [7, 8], auditory and vestibular hair cell survival [9, 10], apical epithelial sodium entry [11], blood pressure [12, 13], iron homeostasis [14-16], male fertility [17, 18], and skin development.…”
Section: Introductionmentioning
confidence: 99%
“…Hair cell damage can result from developmental malformations, post-developmental insults (Dror and Avraham, 2010), or late-onset effects of mutations (Fasquelle et al, 2011) of either cochlear (hearing) or vestibular (balance) hair cells. Regardless of etiology, loss of hair cells is irreversible in mammals.…”
Section: Introductionmentioning
confidence: 99%